Sex, stress and reproductive success - Lovejoy, David A.; Lovejoy, Dalia Barsyte (Hoboken : John Wiley & Sons, 2011)
Any events that challenge the survival of living organisms may be classified as stressors. These stressors could include, for example, lack of food, increased population pressure, predatory pressure, climatic events or in the case of humans, loss of a loved one, lack of financial security or uncertainty in the future. Although most physiological systems are affected by stress, those systems that regulate reproductive physiology and behaviour are the most sensitive. All multicellular organisms show a stress related effect on reproduction, although the more complex organisms, such as mammals, have the most complex effects. The objective of this book is to provide a comparative analysis of the mechanisms by which stress regulates reproduction exploring the evolution of stress perceiving systems from the simplest organisms to humans. Taking an integrated approach, utilising a genes-to-environment overview, the book examines the stressors that occur at all levels of organisation. These theories are used to examine and explain human and animal reproductive behaviour and physiology under stressful conditions providing a well-written, concise introduction to this important subject.
Reprduction under safe conditions -- Reproductive physiology: how it is all supposed to work -- Together -- Physiology of stress: why too much stress stops us from doing things we enjoy -- Reproductive and stress-associated behaviours: integrating conflicting demands -- Animals under strain: life is stressful -- Saving the women and children first: protecting the progeny -- Epigenetic factors in reproductive success: don't ignore your parents -- Species in captivity: stress and reproduction among species -- Used for aquaculture and agriculture -- A cellular understanding of stress and its relationship to reproduction -- Stress and reproduction in human society: implications for the 21st century.
Includes bibliographical references and index.
Print version record.
Keywords: Reproduction; Generative organs -- Effect of stress on; Stress (Physiology); Science; Physiology; Natural history; MEDICAL -- Reproductive Medicine & Technology; Electronic books